PENERAPAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI SISWA KELAS V SD NEGERI 020 TEMBILAHAN HILIR - Masnati Masnati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is a classroom action research, which is motivated by the low ability of reading poetry of class Vstudents of SD Negeri 020 Tembilahan Hilir. The purpose of this research is to improve students' poetry readingability through scramble learning model. This classroom action research is conducted in two cycles, consistingof two meetings in each cycle. Data collection technique used in this research is oral test technique with readingpoetry reading sheet. The result of the research stated that the students' poetry reading ability has improved. Inthe first cycle of meeting I the average reading ability of poetry students get 66.38 score with less category, incycle I meeting II has increased with score score of 73,78 with enough category, on the second cycle of thesecond meeting has increased with the score of 80.68 with good category, and on the second cycle II meetingincreased with a score of 82.97 with good category. Based on the results of this study can be concluded that theapplication of learning model scramble can improve the ability to read poetry students of class V SD Negeri 020Tembilahan Hilir.